IMPROVING STUDENTS ENGLISH PRONUNCIATION THROUGH READING POETRY OF SMA N 1 TOHO - Merry Kristi; Rahayu Apriliaswati; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis research is aimed to investigate how the teaching poetry improved the students’ pronunciation on the tenth grade students of SMA N 1 Toho in academic year 2016/2017. The research was conducted through Classroom Action Research in three cycles. The writer used observation and measurement test as techniques of collecting the data. The writer elaborated the result of observation checklist, field note and students’ assessment as tools of collecting the data in order to get the research findings. The result showed that reading poetry improved students’ pronunciation of [i:] and [æ]. Drill the pronunciation of stanza, give a list, distinguish sound and exaggerated as the strategies to improve the students’ pronunciation of [i:] and [æ]. The average score in the first cycle was 35.08, the second cycle was 46.48, and the third cycle was 70.00. The activities in reading poetry gave positive impacts to the process of teaching and learning on students’ pronunciation. The students could emphasize how to pronounce [i:] and [æ] correctly. Most of students engaged well in teaching and learning process and they were also enthusiastic in reading the poetry. The students also looked confidence in performing their reading poetry in front of the class. As a conclusion, the problems that students faced could be solved through reading poetry. Keyword: pronunciation, reading poetry, [i:] and [æ] sounds.